The Unresponsive Partner: Roles of Social Status, Auditory Feedback, and Animacy in Coordination of Joint Music Performance - Demos, Alexander P.; Carter, Daniel J.; Wanderley, Marcelo M.; Palmer, Caroline (Frontiers in Psychology, 2017)
We examined temporal synchronization in joint music performance to determine how social status, auditory feedback, and animacy influence interpersonal coordination. A partner's coordination can be bidirectional (partners adapt to the actions of one another) or unidirectional (one partner adapts). According to the dynamical systems framework, bidirectional coordination should be the optimal (preferred) state during live performance. To test this, 24 skilled pianists each performed with a confederate while their coordination was measured by the asynchrony in their tone onsets. To promote social balance, half of the participants were told the confederate was a fellow participant - an equal social status. To promote social imbalance, the other half was told the confederate was an experimenter - an unequal social status. In all conditions, the confederate’s arm and finger movements were occluded from the participant's view to allow manipulation of animacy of the confederate’s performances (live or recorded). Unbeknownst to the participants, half of the confederate’s performances were replaced with pre-recordings, forcing the participant into unidirectional coordination during performance. The other half of the confederate’s performances were live, which permitted bidirectional coordination between performers. In a final manipulation, both performers heard the auditory feedback from one or both of the performers’ parts removed at unpredictable times to disrupt their performance. Consistently larger asynchronies were observed in performances of unidirectional (recorded) than bidirectional (live) performances across all conditions. Participants who were told the confederate was an experimenter reported their synchrony as more successful than when the partner was introduced as a fellow participant. Finally, asynchronies increased as auditory feedback was removed; removal of the confederate’s part hurt coordination more than removal of the participant’s part in live performances. Consistent with the assumption that bidirectional coupling yields optimal coordination, an unresponsive partner requires the other member to do all the adapting for the pair to stay together.